A study to validate thoracic trauma severity score in chest trauma patients - Sharma, Amit K.; Rathore, Shaitan S.; Verma, Vijay; Yadav, Parul (International Surgery Journal, 2020)
Background: Aim of this study was to validate thoracic trauma severity score (TTSS) in assessing the requirement of mechanical ventilation, mortality, and predicting prognosis in chest injury patients. Methods: This study was conducted in department of general surgery, Dr. S. N. Medical College, Jodhpur, Rajasthan, from December 2018 to September 2019. This was a single centred, prospective, observational study, conducted in 110 patients, aged >18 years, of isolated chest injury, excluding polytrauma patients. Data was summarized in the form of proportions, histograms and tables to show relationships of parameters with results. Data was presented as mean±SD and proportions as appropriate. Chi square test, z test or t tests were used wherever necessary for association analysis between categorical variables. Diagnostic test characteristics for mortality and complications was calculated from the ROC curves. A two sided of p values of less than 0.05 was considered statistically significant. Results: Most common mode of chest injury was blunt trauma and most common age group affected was 42-54 years. Maximum mortality was seen in TTSS between 16-20, shows higher the TTSS more the mortality. Ventilator requirement was more in high TTSS. Patients with higher TTSS had longer hospital stay as compared to patients with lower TTSS. Conclusions: On application of TTSS on admission, TTSS had direct correlation with need for oxygenation, ventilator need, duration of hospital stay, mortality or outcome in chest trauma patients. Thus we recommend TTSS as a good useful score for evaluation of prognosis, outcome and mortality in chest trauma patients.